2017
DOI: 10.1111/aos.13363
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitecture of epithelial inflammatory infiltration indicates the aetiology of infectious keratitis

Abstract: Confocal microscopy analysis in infectious keratitis of various aetiologies revealed quantitative and qualitative differences in inflammatory cell infiltration expressed in different ratio of round/non-round inflammatory cells. In vivo microscopic analysis of both the corneal epithelial layer cytopathology and the cytology of inflammatory infiltration provides a fast and specific differentiation of keratitis aetiology that may increase the accuracy in the selection of the initial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The accuracy of transfer model was comparable to that of experienced ophthalmologist and better than under-experienced ophthalmologist. It has been reported that activated DCs and inflammatory cells are important biomarkers for monitoring inflammatory activity and clinical severity of corneal diseases [ 7 , 8 ]. Our DTL models proposed automated solutions for the evaluation of corneal inflammatory cellular components, which may support under-experienced ophthalmologists in decision making regarding the management of corneal diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of transfer model was comparable to that of experienced ophthalmologist and better than under-experienced ophthalmologist. It has been reported that activated DCs and inflammatory cells are important biomarkers for monitoring inflammatory activity and clinical severity of corneal diseases [ 7 , 8 ]. Our DTL models proposed automated solutions for the evaluation of corneal inflammatory cellular components, which may support under-experienced ophthalmologists in decision making regarding the management of corneal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo confocal microscopy (IVCM) enables noninvasive analysis of different corneal layers in exquisite detail and allows in vivo detection of even subtle microstructural changes in pathological states [ 3 , 4 ]. IVCM image analysis reveals dendritic cells (DCs) activation and inflammatory cells infiltration in pathologic and infectious conditions such as dry eye [ 5 , 6 ], infectious keratitis of various aetiologies [ 7 , 8 ], and contact lens-induced corneal changes [ 9 ]. The inflammatory cellular components are considered as excellent indicators of inflammatory activity and clinical severity [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1B–F ). Inflammatory round cells were described as small (<10 µm 13 ), hyperreflective, oval-shaped cells with no visible fibrils, ring shape, or double-walled structure ( Fig. 1G ).…”
Section: Methodsmentioning
confidence: 99%
“…Confocal microscopy is a novel non-invasive corneal imaging examination method [9][10][11]. Due to high resolution and magnification, it reveals the corneal changes at the cellular level under three-dimensional space and real-time conditions; similar results could be obtained in the cloudy corneal tissue, making it a commonly used tool for the clinical study of corneal lesions [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Confocal microscopy plays a major role in evaluating keratitis and corneal nerves [9][10][11][12][13][14], but there is only one study about its use for AACC which focused on Langerhans cells and keratocytes [15]. Our study aimed to investigate corneal epithelial cells, subepithelial nerve fiber plexus, stromal cells, and endothelial cells of the AACC and fellow eyes and healthy controls using confocal microscopy.…”
Section: Introductionmentioning
confidence: 99%